Quality Improvement of Capsular Polysaccharide in Streptococcus pneumoniae by Purification Process Optimization - Lee, Chankyu; Chun, Hee Jin; Park, Minchul; Kim, Rock Ki; Whang, Yoon Hee; Choi, Seuk Keun; Baik, Yeong Ok; Park, Sung Soo; Lee, Inhwan (Frontiers in Bioengineering and Biotechnology, 2020)
Streptococcus pneumoniae is the causative agent of many diseases, most notably pneumonia. Vaccine development using pneumococcal capsular polysaccharides (CPS) is a current focus, but purifying CPS of sufficient quality has been challenging. A purification process for CPS comprising conventional methods such as ultrafiltration, CTAB precipitation, and chromatography was previously established; however, this method resulted in high cell wall polysaccharide (CWPS) contamination, especially for serotype 5. Thus, a better purification method that yields CPS of a higher quality is needed for vaccine development. In this study, we significantly reduced CWPS contamination in serotype 5 CPS by improving the ultrafiltration and CTAB precipitation steps. Moreover, by applying an additional precipitation process to further remove other impurities, serotype 5 CPS was obtained with a high purity suitable for application in pneumococcal vaccine manufacturing. This improved method was also successfully applied to 14 other serotypes (1, 3, 4, 6A, 6B, 7F, 9V, 11A, 14, 18C, 19A, 19F, 22F, and 23F). To assess the immunogenicity of the CPS from the 15 serotypes, two sets of 15-valent pneumococcal conjugate vaccines were prepared using the previous purification method and the improved method developed here; these vaccines were administered to a rabbit model. Enzyme-linked immunosorbent assay and opsonophagocytic assay demonstrated higher immunogenicity of the conjugate vaccine prepared using CPS produced by the improved purification process.